Construction of Passighat bridge in Arunachal Pradesh: a case study on well sinking in bouldery strata - Kumar, M. Kishore; Rao, C.H. Hanumantha (Journal of Structural Engineering, 2024)
The most uncertain element in bridge construction is foundation and the present case study is a classic example of faulty design data on soil parameters leading to contractual disputes and resulting inordinate delay in its completion. The construction went on for about two decades mostly lingering on well sinking at Pier wells P3 and P4 mostly due to nature of terrain and also owing to tough and limited working period. The model studies on scour depth, stability analysis and alternatives suggested to counter sinking problems presented in this paper would be of quite interest to the learned readers.